2012
DOI: 10.1038/gim.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interpretation of newborn screening results without analyte cutoff values

Abstract: Purpose: To improve quality of newborn screening by tandem mass spectrometry with a novel approach made possible by the collaboration of 154 laboratories in 49 countries. Methods: A database of 767,464 results from 12,721 cases affected with 60 conditions was used to build multivariate pattern recognition software that generates tools integrating multiple clinically significant results into a single score. This score is determined by the overlap between normal and disease ranges, penetration within the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 23 publications
1
98
0
Order By: Relevance
“…The detection rate of MAD deficiency may be improved by applying more sophisticated algorithms weighing several acylcarnitines together. Using an improved interpretive tool (Marquardt et al 2012), we retrospectively detected one patient and confirmed the increased sensitivity of this tool. This is especially important because the incidence of the riboflavin-responsive form of MAD deficiency is high in Taiwan (Liang et al 2009;Lan et al 2010) and Southern China (Wang et al 2011) owing to a high incidence of the p.A84T mutation in the ETFDH gene (a carrier rate of 1 in 74), and the treatment with carnitine and riboflavin is easy and effective.…”
Section: The Occurrences Of False-negative Cases In Nbsmentioning
confidence: 63%
See 1 more Smart Citation
“…The detection rate of MAD deficiency may be improved by applying more sophisticated algorithms weighing several acylcarnitines together. Using an improved interpretive tool (Marquardt et al 2012), we retrospectively detected one patient and confirmed the increased sensitivity of this tool. This is especially important because the incidence of the riboflavin-responsive form of MAD deficiency is high in Taiwan (Liang et al 2009;Lan et al 2010) and Southern China (Wang et al 2011) owing to a high incidence of the p.A84T mutation in the ETFDH gene (a carrier rate of 1 in 74), and the treatment with carnitine and riboflavin is easy and effective.…”
Section: The Occurrences Of False-negative Cases In Nbsmentioning
confidence: 63%
“…Therefore, we retrospectively evaluated our newborn screening data using the Region 4 post-analytic tool (Marquardt et al 2012). One newborn (FN-5) was found to have a high MAD deficiency score, and the diagnosis was later confirmed by mutation analysis.…”
Section: The False-negative Casesmentioning
confidence: 99%
“…The most sensitive indicator to detect CPT-II deficiency is an elevated (C16 + C18:1)/C2 ratio (Gempel et al 2002;Marquardt et al 2012). However, a study of simultaneous analysis of plasma and dried blood spot (DBS) from individuals with known metabolic diagnoses suggested that this indicator can sometimes be unreliable because some patients' (C16 + C18:1)/C2 ratio may be normal in DBSs (de Sain-van der Velden et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's (C16 + C18:1)/C2 ratio of 0.34 was indeed below the 95th percentile of the reference range for DBSs reported in that paper (0.37). We also analyzed our patient's NBS acylcarnitine profile with the productivity and post-analytical interpretive tools of the Region 4 Stork (R4S) collaborative laboratory quality improvement of newborn screening by tandem mass spectrometry (https://www.clirr4s.org/) (Marquardt et al 2012;Hall et al 2014). This produced the results presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…R4S has developed Post-Analytical (PA) tools to assist programs in making these decisions, and in the case of Minnesota's MS/MS panel, to eliminate cutoffs all together (Rinaldo 2013). A recent paper documents how the PA tools use multivariate pattern-recognition software to create case scores based on the MS/MS results uploaded into R4S, in particular the degree of overlap of informative analytes (Marquardt et al 2012). As with many other programs, Washington is uneasy with eliminating cutoff algorithms, but is interested in finding ways to integrate the PA tools into the program as an additional resource in the evaluation of test results.…”
Section: Post-analytical Toolsmentioning
confidence: 99%